Epidemiological Aspects of Overweight and Obesity among the Adult Population of the Voronezh Region - N. V. Gabbasova; N. V. Dzen (Эпидемиология и вакцинопрофилактика)
Relevance Obesity has a major impact on the health and well-being of the population, and the prevention of overweight and obesity is a public health priority in many countries around the world.Purpose: was to study the prevalence of obesity among the adult population of the Voronezh region for the period 1996 – 2017, a comparative assessment of the structure of eating behavior in people with normal weight and overweight/obesity.Methods. The research material was data the annual form No. 12 of Rosstat for 1996 through 2017. In order to study eating disorders, 150 people aged from 20 to 61 years were surveyed using the Dutch questionnaire. The main types of eating behavior among the respondents were determined. Ideal weight was calculated by Brock's field formula (1891), the upper limit of normal body weight was considered ideal weight plus 15% ideal weight. Statistical data processing was performed using Microsoft Excel 2007.Results. The study on the prevalence of obesity was conducted among the adult population of the Voronezh region for the period 1996-2017. The Prevalence of obesity over the period studied has increased by 8 times, the average annual growth rate over the last 4 years was 30,04%. The study of the types of food behavior in respondents with normal and overweight / obesity showed that in most cases the respondents observed pathological types (most often mixed and external). A comparative assessment of the types of eating behavior did not show any significant differences between the groups.Conclusions. The increase in the prevalence of obesity, the high average annual growth rate indicates the increased impact of risk factors on the formation of obesity and the ineffectiveness of the strategy and tactics of dealing with this pathology. The absence of significant differences in the structure of eating behavior does not allow us to consider it a risk factor for obesity.